Hypokalemic Paralysis due to Primary Sjögren Syndrome: Case Report and Review of the Literature - A. Garza-Alpirez; A. C. Arana-Guajardo; J. A. Esquivel-Valerio; M. A. Villarreal-Alarcón; D. A. Galarza-Delgado (Case Reports in Rheumatology)
Tubulointerstitial nephritis (TIN) is the main renal involvement associated with primary Sjögren syndrome (pSS). TIN can manifest as distal renal tubular acidosis (RTA), nephrogenic diabetes insipidus, proximal tubular dysfunction, and others. We present a 31-year-old female with hypokalemic paralysis due to distal RTA (dRTA). She received symptomatic treatment and hydroxychloroquine with a good response. There is insufficient information on whether to perform a kidney biopsy in these patients or not. The evidence suggests that there is an inflammatory background and therefore a potential serious affection to these patients, such as hypokalemic paralysis. We found 52 cases of hypokalemic paralysis due to dRTA in pSS patients. The majority of those patients were treated only with symptomatic medication. Patients who received corticosteroids had stable evolution even though they did not have another symptomatology. With such heterogeneous information, prospective studies are needed to assess the value of adding corticosteroids as a standardized treatment of this manifestation.